Application of Boundary Element Method to Inviscid Flow Around Thin Airfoils - Ahmad Yazid, Aznijar (2004)

(untitled)
With the continuous development of faster and cheaper computers of late, application of computational methods in solving engineering problems has become increasingly popular. New techniques are continuously being researched and developed in order to bring the numerical solution nearer to reality. A Boundary Element Method is developed in the research to solve aerodynamic problems. Investigations revealed that the solution obtained using boundary element method is slightly superior to the solution provided by the currently used Panel Method. It was also found that the new technique also manages to obtain better result employing a lower number of nodes during solution, reducing the computational time. However, the adoption of potential theory means that the stall conditions of airfoils could still not be predicted at all.